The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1093/bib/bbx111
|View full text |Cite
|
Sign up to set email alerts
|

Systematic comparative study of computational methods for T-cell receptor sequencing data analysis

Abstract: High-throughput sequencing technologies have exposed the possibilities for the in-depth evaluation of T-cell receptor (TCR) repertoires. These studies are highly relevant to gain insights into human adaptive immunity and to decipher the composition and diversity of antigen receptors in physiological and disease conditions. The major objective of TCR sequencing data analysis is the identification of V, D and J gene segments, complementarity-determining region 3 (CDR3) sequence extraction and clonality analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Additionally, Mora and Walczak showed that the Rényi entropy (the mathematical foundation of Hill-Diversity profiles) can be constructed, in some cases, from rank-frequency plots (70) thereby establishing a direct mathematical link between clonal frequency distribution and diversity indices. Another interesting novel diversity analysis method is the clonal plane and the polyclonal monoclonal diversity index developed by Afzal et al (71). Briefly, these two related concepts represent repertoire diversity in a coordinate system spanned by species richness and evenness.…”
Section: Measuring Immune Repertoire Diversitymentioning
confidence: 99%
“…Additionally, Mora and Walczak showed that the Rényi entropy (the mathematical foundation of Hill-Diversity profiles) can be constructed, in some cases, from rank-frequency plots (70) thereby establishing a direct mathematical link between clonal frequency distribution and diversity indices. Another interesting novel diversity analysis method is the clonal plane and the polyclonal monoclonal diversity index developed by Afzal et al (71). Briefly, these two related concepts represent repertoire diversity in a coordinate system spanned by species richness and evenness.…”
Section: Measuring Immune Repertoire Diversitymentioning
confidence: 99%
“…Thus, exposures to the auto-Ag (Ag1 or Ag2) decreased the diversity of the endogenous Tfh repertoire compared to the PBS group. To establish this finding, we used multiplex iRepertiore PCRs and subsequent MiTCR analysis for preparing libraries and annotating TCRβ sequences ( Bolotin et al, 2013 ), which ensures to yield the highest possible diversity of TCRβ clonotypes ( Afzal et al, 2019 ). To confirm this decrease in diversity of the endogenous Tfh repertoire, we reanalyzed our data for Ag1 with a more precise analysis tool MiXCR that is advantageous for error corrections and adjusts for a more accurate clonal composition ( Bolotin et al, 2013 ; Bolotin et al, 2015 ; Team I, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…RNA was used for RACE-PCR according to previously described protocols [ 57 , 58 ]. List of RACE-PCR oligonucleotides are provided in Table S9 .…”
Section: Methodsmentioning
confidence: 99%